Philippine Readiness for the 4th Industrial Revolution: A Case Study - Kim, Junmo (Animo Repository, 2019)
This explores how the fourth industrial revolution (FIR) affects developing countries, specifically in the case of the Philippines. It presents an alternative account to the claim that the world is ready to enter the FIR. The analyses show that the readiness of the Philippines for FIR is not the same as developed and industrialized countries. The authors argue that developing countries like the Philippines will not go through FIR in the same way the developed countries do, given their different economic context and limited access to technological advances. Just as the Philippines participated in the third industrial revolution in a manner that is different from the developed countries, it will also participate in the FIR in a different manner. This article will provide insights to its possible participation and its implications.